1996
DOI: 10.1111/j.1532-5415.1996.tb05631.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Dementia Care in Nursing Homes

Abstract: The A.G.E. program reduces the prevalence of behavior disorders and the use of antipsychotic drugs and restraints. It is practical, feasible, and appears to improve the lives of patients with dementia in nursing homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
157
2
5

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(172 citation statements)
references
References 29 publications
8
157
2
5
Order By: Relevance
“…In light of the known side-effects and rather serious risks associated with antipsychotic drug use (Brodaty et al, 2003;Katz, 2004), this is an important ethical question, especially because there are alternative ways of managing the behavioral disturbances that might occur in dementia. Non-pharmacological approaches have been used successfully to reduce behavioral disturbances (Rovner et al, 1996;Sloane et al, 2004). Furthermore, most studies proving the effectiveness of antipsychotics have been performed over shorter periods of time, while studies lasting over a whole year (Ballard et al, 2001) and discontinuation studies Thapa et al, 1994) have found no benefits from ongoing antipsychotic medication for a majority of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the known side-effects and rather serious risks associated with antipsychotic drug use (Brodaty et al, 2003;Katz, 2004), this is an important ethical question, especially because there are alternative ways of managing the behavioral disturbances that might occur in dementia. Non-pharmacological approaches have been used successfully to reduce behavioral disturbances (Rovner et al, 1996;Sloane et al, 2004). Furthermore, most studies proving the effectiveness of antipsychotics have been performed over shorter periods of time, while studies lasting over a whole year (Ballard et al, 2001) and discontinuation studies Thapa et al, 1994) have found no benefits from ongoing antipsychotic medication for a majority of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the limited evidence of efficacy does limit the potential value of quetiapine, this is probably helpful in indicating that atypical agents have a less detrimental impact on quality of life than typical antipsychotics. Important studies have highlighted the potential of specific non-pharmacological intervention programs to improve key outcomes such as the use of unnecessary antipsychotic drugs (Rovner et al 1996;Fossey et al, 2006), mood (Teri et al, 1997;2003) and behavioral symptoms (Cohen-Mansfield et al, 2007) with person-centered training for care staff, or structured approaches such as exercise, social interaction, pleasant events or assessment of needs, but disappointingly few studies have directly evaluated the impact of these interventions on quality of life directly, or the impact of stopping antipsychotics on quality of life amongst care home residents with dementia. The Focused Intervention Training and Support (FITS) study, in a cluster randomized trial, demonstrated the capacity of a training program focused on person-centered care to significantly reduce the use of antipsychotic drugs in care homes (Fossey et al, 2006).…”
Section: Antipsychotics and Quality Of Lifementioning
confidence: 99%
“…While subjects in both groups received psychotropics, controls were more than twice as likely to receive antipsychotics or be physically restrained compared with subjects in the treatment group. 48 Changes to the level of stimulation can have varying effects on patients with dementia and disturbed behaviour. While studies examining methods to increase stimulation by use of activity groups, exercise and social interaction have demonstrated positive results, 43,48 other studies suggest reduced stimulation may decrease agitation and other problematic behaviours.…”
Section: The Canadian Journal Of Neurological Sciencesmentioning
confidence: 99%
“…48 Changes to the level of stimulation can have varying effects on patients with dementia and disturbed behaviour. While studies examining methods to increase stimulation by use of activity groups, exercise and social interaction have demonstrated positive results, 43,48 other studies suggest reduced stimulation may decrease agitation and other problematic behaviours. 49 Increasing the level of stimulation may occasionally have adverse effects.…”
Section: The Canadian Journal Of Neurological Sciencesmentioning
confidence: 99%